Redécouverte d’un tibia et d’un fémur provenant du site de La Madeleine, Dordogne - Aurélie Fort (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
During the inventory of the anthropological collections of the Musée de l’Homme (Muséum national d’histoire naturelle, Paris) in 2006, a right tibia and a right femur apparently coming from the site of La Madeleine, Dordogne, were found. However these two remains are not mentioned in any article, nor any catalogue, and do not appear in any registers. The first mention appears in 1874 in an article of Hamy in the Bulletins de la Société d’Anthropologie de Paris, then in 1875 in the Reliquiae Aquitanicae from Lartet and Christy (who had excavated the site after its discovery in 1863). They are thereafter forgotten and disappear from the inventories. A morphological comparison with the fragments indexed in the Musée de l’Homme (a left fragment of tibia and a left fragment of femur), as well as the comparison with the measurements carried out by Hamy confirms that these bones come from La Madeleine.